THE ROLE OF CONTENT MARKETING IN ATTRACTING AND RETAINING CUSTOMERS - Mamatkulova Shoira Jalolovna (Western European Studies, 2024)
Content marketing has emerged as a critical strategy for businesses to attract and retain customers in today's digital landscape. This article explores the role of content marketing in driving customer acquisition and retention. It examines how businesses can create valuable and engaging content to capture the attention of their target audience, establish trust and credibility, and ultimately foster long-term relationships. By analyzing case studies and industry trends, this article provides insights into the effectiveness of content marketing strategies and offers practical recommendations for businesses looking to leverage content to enhance customer engagement and loyalty.
Keywords: content marketing; customer acquisition; customer retention